Body language in the Maqamat of Hamadani: El maqama el karadia as a model - SAHRAOUI, Radia (Journal of Human Sciences, 2020)
This study is built upon a methodological approach concerning the use of  body language as a set of emotional and psychological message on one side and semantic load on the other.Consequently, this article presents an analytical interpretation of body language as it appears in the maqamat of  Badi’ Al Zaman Al  Hamadani when he adapts his body to the various psychological and emotions around whitch revolve the of his Maqamat.